RESEARCH OF PROCESSES OF OBTAINING SAPONINS FROM THE ROOTS OF SAPONARIA OFFICINALIS L (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article discusses about the processes of extraction saponins from roots Saponaria officinalis L.an insisting method at temperature 100 0C and a method repercolation. Definitions of frequency rate of pouring water at an extraction a method repercolation for the purpose of the maximum extraction of operating substances (saponins). And comparison of technological properties of the extracts received by these methods.